Substance use and sexual risk behavior in HIV-positive men who have sex with men: an episode-level analysis. - Boone, Melissa R; Cook, Stephanie H; Wilson, Patrick (AIDS and behavior, 2013)
Men who have sex with men (MSM) make up nearly half of all people living with HIV in the United States. The prevalence of the epidemic in this population makes it vitally important to understand the transmission of the infection and to develop methods to prevent its spread. The current study uses longitudinal diary methods to examine relationships between substance use and unprotected anal intercourse in a sample of 158 HIV-positive, mostly ethnic minority MSM. Results indicate that both general substance use and use of specific drugs (i.e., inhalants, cocaine, crack, and club drugs) have a substantial impact on the sexual risk behavior of this population.
Keywords: Adult; Age Factors; Amphetamine-Related Disorders; Cocaine-Related Disorders; Crack Cocaine; HIV Seropositivity; Homosexuality, Male; Humans; Inhalant Abuse; Logistic Models; Male; Marijuana Abuse; Middle Aged; New York City; Prospective Studies; Street Drugs; Substance-Related Disorders; Unsafe Sex; Young Adult